UPAYA MENINGKATKAN HASIL BELAJAR IPS SISWA DENGAN MODEL PEMBELAJARAN JIGSAW KELAS VI SEKOALAH DASAR NEGERI 18 LUBUKLINGGAU - Tuti Triyani (Jurnal Perspektif Pendidikan, 2021)
This study aims to improve the social studies learning outcomes of Class VI students of SD Negeri 18 Lubuklinggau by using the Jigsaw learning model. The research method used in this study is a classroom action research method (Action Research) using the Jigsaw learning model. Data collection techniques were carried out by means of observation and tests. Based on the results of research using the Jigsaw learning model in class VI students at SD Negeri 18 Lubuklinggau, it turned out to be able to improve student learning outcomes. Student learning outcomes continue to increase in each cycle, in the first cycle of the first meeting the average student learning outcomes of 51.86, the second meeting of 59.45 then in the second cycle of the first female student learning outcomes of 62.14 and at the second meeting 67 .95. and in cycle 3 the first meeting the average student learning outcomes was 71.14 and the second meeting was 85.76